High-temperature solid oxide fuel cells fundamentals, design, and applicatons - Singhal, Subhash C.; Kendall, Kevin, 1943- (New York : Elsevier Advanced Technology, 2003)
The growing interest in fuel cells as a sustainable source of energy is pulling with it the need for new books which provide comprehensive and practical information on specific types of fuel cell and their application. This landmark volume on solid oxide fuel cells contains contributions from experts of international repute, and provides a single source of the latest knowledge on this topic.
Introduction -- History of SOFCs -- Thermodynamics -- Electrolyte -- Cathode -- Anode -- Interconnect (ceramic, metallic) -- Electrode Polarizations -- Fuels and Fuel Processing -- Cell and Stack Designs -- Cell and Stack Modelling -- Cell and Stack Testing -- Applications and Demonstrations.
Includes bibliographical references and index.
Keywords: Solid oxide fuel cells; Electronic books